Stochastic variational approach applied to 2, 3 and 4 alpha particles - Ventura, Daneele S. [UNESP] (2011)
A stochastic variational method is applied to calculate the binding energies and root-mean-square radii of 2, 3 and 4 alpha particles using an S-wave Ali-Bodmer potential. The results agree with other calculations. We discuss the application of the present method to study the universality in weakly-bound three and four-body systems in the context of ultracold atomic traps.